Enhancing Facial Identification Systems with YOLOv8: A Cutting-Edge Approach - Huda S. Mithkhal; Ahmed H Y Al-Noori; Emad Tariq Al-Shiekhly (مجلة النهرين للعلوم الهندسية)
Face recognition and identification have recently become the most widely employed biometric authentication technologies, especially for access to persons and other security purposes. It represents one of the most significant pattern recognition technologies that uses characteristics included in facial images or videos to detect the identity of individuals. However, most of the traditional facial algorithms have faced limitations in identification and verification accuracy.